Mitogen Activated Protein kinase signal transduction pathways in the prostate - Maroni, Paul D (BioMed Central, 2004)
The biochemistry of the mitogen activated protein kinases ERK, JNK, and p38 have been studied in prostate physiology in an attempt to elucidate novel mechanisms and pathways for the treatment of prostatic disease. We reviewed articles examining mitogen-activated protein kinases using prostate tissue or cell lines. As with other tissue types, these signaling modules are links/transmitters for important pathways in prostate cells that can result in cellular survival or apoptosis. While the activation of the ERK pathway appears to primarily result in survival, the roles of JNK and p38 are less clear. Manipulation of these pathways could have important implications for the treatment of prostate cancer and benign prostatic hypertrophy.